ERM Money Supplies and the Transition to EMU - Masson, Paul (IMF Working Papers; Working Paper ;, 1994)
Stage 2 of monetary union in the Europe is to involve greater monetary cooperation; the paper examines the case for using the M3 money supply aggregated across 'core ERM' countries- -those with low inflation and absence of realignments- -as a vehicle for that cooperation. First, the existence of a satisfactory long-run money demand relationship and short-run dynamic equation is verified. The resulting demand equations have at least as satisfactory econometric properties as those for France and Germany separately. Second, the predictive power of the core-ERM aggregate relative to French and German inflation is examined; it is shown that the aggregate helps to predict German inflation, over and above the predictive power of German M3. Thus, core-ERM M3 has value as an indicator for the anchor country in hitting its own domestic objective, quite separate from any concern about economic developments in neighboring countries.